2021
DOI: 10.1038/s41598-021-01883-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral vaccination of piglets against Mycoplasma hyopneumoniae using silica SBA-15 as an adjuvant effectively reduced consolidation lung lesions at slaughter

Abstract: Mycoplasma (M.) hyopneumoniae is the main pathogen of porcine enzootic pneumonia (PEP). Its controlling is challenging, and requires alternative strategies. This study aimed to develop an oral vaccine against M. hyopneumoniae using a nanostructured mesoporous silica (SBA-15) as an adjuvant, and compare its effect with an intramuscular (IM) commercial vaccine (CV). Fifty 24 day-old M. hyopneumoniae-free piglets composed five equal groups for different immunization protocols, consisting of a CV and/or oral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Accordingly, previous studies have shown that animals infected with M. hyopneumoniae have a predominance of the species over other species, reducing bacterial diversity in the lung [ 9 , 27 ]. It is known that M. hyopneumoniae stimulates the immune system, generating the release of various pro-inflammatory cytokines [ 28 31 ], induces apoptosis [ 32 ], nitric oxide stimulation [ 33 ], which promote lung damage in infected individuals. Likewise, lung damage was also observed in the present study, as animals positive for M. hyopneumoniae had a higher degree of pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous studies have shown that animals infected with M. hyopneumoniae have a predominance of the species over other species, reducing bacterial diversity in the lung [ 9 , 27 ]. It is known that M. hyopneumoniae stimulates the immune system, generating the release of various pro-inflammatory cytokines [ 28 31 ], induces apoptosis [ 32 ], nitric oxide stimulation [ 33 ], which promote lung damage in infected individuals. Likewise, lung damage was also observed in the present study, as animals positive for M. hyopneumoniae had a higher degree of pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…A lower degree of lung injury, associated with the increase in IgA levels in animals that received the oral vaccine, was observed in animals that received the new vaccine in the previously conducted study [ 16 ]. In the present study, vaccinated piglets also showed a lower degree of lung injury, regardless of the vaccination protocol.…”
Section: Discussionmentioning
confidence: 97%
“…There is still little data in the literature regarding the use of SBA-15 associated with antigens in the composition of oral vaccines, especially for animals such as the one produced in the present study. A previous study of characterization and use of the same oral vaccine under laboratory conditions of controlled infection showed promising results in stimulating immunity and reducing lung lesions at slaughter [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations